2017
DOI: 10.1080/24740527.2017.1384297
|View full text |Cite
|
Sign up to set email alerts
|

Treatment expectations but not preference affect outcome in a trial of CBT and exercise for pain

Abstract: Background: Patients’ beliefs and attitudes toward a treatment can affect treatment response. In unblinded trials this can affect outcomes. Aims: The aim of this analysis was to examine the association between treatment preference and expectation and outcome in a trial of pain treatments. Methods: In a randomized trial (ISRCTN67013851) of four treatments for chronic widespread pain, participants were asked which they would prefer and what improvement they expect from each. The proportion of participants report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…However, previous research among clinical cohorts has demonstrated that receiving support preferences may impact patient perceptions about the usefulness of an intervention [ 60 ] and improve adherence [ 28 , 61 ]. While a meta-analysis revealed that patients receiving their preferences demonstrated improved treatment satisfaction, adherence, and outcomes with moderate effect sizes [ 28 ], other research found that receiving the preferred option does not always impact outcomes [ 61 , 62 ]. A 2019 study of patients with anxiety and depression compared adherence and outcomes when patients chose their preferred support [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research among clinical cohorts has demonstrated that receiving support preferences may impact patient perceptions about the usefulness of an intervention [ 60 ] and improve adherence [ 28 , 61 ]. While a meta-analysis revealed that patients receiving their preferences demonstrated improved treatment satisfaction, adherence, and outcomes with moderate effect sizes [ 28 ], other research found that receiving the preferred option does not always impact outcomes [ 61 , 62 ]. A 2019 study of patients with anxiety and depression compared adherence and outcomes when patients chose their preferred support [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference was even greater in CBT trials and was independent of depression severity and dropout rates. In a trial in patients with chronic widespread pain, participants could choose between four options (CBT, exercise, a combination of both, or TAU), and the treatment preference had no effect on treatment outcome, while improvement expectations did (121). Neither of the studies elaborated on the placebo effect size under preference–choice conditions.…”
Section: Nonspecific Solutions For the Control Of The Specific Placebmentioning
confidence: 99%
“…A Likert scale will be used for the patient’s expectation regarding the treatment: the patient will be questioned about their expectation of the intervention with the following question: ‘With the dry cupping therapy application, do you think you will’: with the possible answers being: (1) get worse; (2) get a little worse; (3) not improve or get worse; (4) improve a little and (5) improve a lot 64…”
Section: Methodsmentioning
confidence: 99%